Effects of Increasing Zinc, Using Zn Hydroxychloride, on Growth Performance, Carcass Characteristics, and Economic Return of Pigs Housed in a Commercial Environment - H. S. Cemin; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 2,430 pigs (PIC 337 × 1050; initially 66.3 lb BW) were used in a 113-d growth trial to determine the effects of increasing Zn on growth performance and carcass characteristics of finishing pigs. Two barns were used for a total of 18 pens per treatment with 27 pigs per pen. Pigs were allotted by average initial BW and assigned to 1 of 5 dietary treatments consisting of 50, 87.5, 125, 162.5, or 200 ppm added Zn from Zn hydroxychloride (Intellibond Z, Micronutrients, Indianapolis, IN). Experimental diets were fed from d 0 to 113 in 5 phases and contained a trace mineral premix that did not contain any added Zn. Overall (d 0 to 113), there were marginally significant quadratic responses in ADFI (P = 0.073) and F/G (P = 0.067), with the lowest ADFI and best F/G observed when 87.5 and 125 ppm of Zn were fed, respectively. There was no evidence for differences in carcass characteristics (P>0.10). Regarding economic effects, there was a marginally significant (P = 0.075) quadratic response in feed cost per pig and feed cost per pound of gain (P = 0.088). The lowest feed cost per pig and feed cost per pound of gain were observed when 87.5 and 125 ppm of Zn was fed, respectively. In conclusion, there were no improvements in ADG when feeding beyond 50 ppm added Zn; however, feeding 125 ppm Zn resulted in the best F/G.
Keywords: Zn; zinc; finishing pig; growth performance